Heterorhabditis Bacteriophora: An Ecofriendly Biological Control Agent - Elizabeth Gerdes; Devang Upadhyay; Leonard D. Holmes; Sivanadane Mandjiny; Rebecca Bullard-Dillard; Meredith Storms; Michael Menefee (European Scientific Journal, ESJ, 2017)
The entomopathogenic nematode, Heterorhabditis bacteriophora, is an environmentally safe alternative to chemical pesticides. It is half of a symbiotic relationship with the bacteria, Photorhabdus luminescens which lives in the nematode gut. Heterorhabditis bacteriophora has a wide range of susceptible insects making it a very effective alternative to current biological control practices. The nematode has been proven to be safe to humans, nontarget insects, wildlife, fauna, and water. For this reason, as well as consumers’ increasing consciousness of health issues, Heterorhabditis bacteriophora should be considered as a viable alternative and researched more thoroughly.